Waste not, pollute not [animal waste recycling for power production]. - Goldstein, H. (IEEE spectrum)
Recycling animal waste can keep water cleaner and generate electricity off the grid. The paper describes the use of animal waste in the form of biogas at AA Dairy to produce electricity. The gas is burned in a diesel engine converted to run on methane. 10-20% of the electricity produced in summer is sold to the grid, the figure rises to 35-40% in winter. The paper then discusses the wider picture of bioenergy conversion at farms in the USA. The chemical impact on groundwater and soil stewardship are also discussed